2016
DOI: 10.4018/ijavet.2016040104
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Introduction to Q Methodology

Abstract: Q methodology is a method to systematically study subjective matters such as thoughts and beliefs on any given topic. Q methodology can be used for both theory building and theory testing. The purpose of this paper was to give a brief overview of Q methodology to readers with various backgrounds. This paper discussed several advantages of Q methodology that makes it attractive to researchers and practitioners who are interested in understanding different perspectives or behavioral patterns toward any given top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
14
0
3
Order By: Relevance
“…The method can be used as a mixed method with a limited number of respondents (Davis & Michelle, 2011), useful for evaluating the proposed IS artifact in the demonstration process of DSR. Besides, the mapping supports the previous study on the use of the Q-method for theory building (Yang, 2016), as shown in Table 1. The Q-method contributes 44% to the invention of knowledge as one of the main objectives of DSR (Gregor & Hevner, 2013;Gregory, 2011) in the IS community.…”
Section: 3supporting
confidence: 86%
See 2 more Smart Citations
“…The method can be used as a mixed method with a limited number of respondents (Davis & Michelle, 2011), useful for evaluating the proposed IS artifact in the demonstration process of DSR. Besides, the mapping supports the previous study on the use of the Q-method for theory building (Yang, 2016), as shown in Table 1. The Q-method contributes 44% to the invention of knowledge as one of the main objectives of DSR (Gregor & Hevner, 2013;Gregory, 2011) in the IS community.…”
Section: 3supporting
confidence: 86%
“… The IS strategy, Management, and Acquisition. The Q-method consists of a concourse or a list of statements, opinions, or the sum of all that people say or think about the investigated topic collected from various sources (Watts & Stenner, 2012;Yang, 2016). Statements are essential to preparation and can be used to represent the feelings and opinions of the user/object of study (Watts & Stenner, 2012).…”
Section: 11mentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have employed qualitative techniques such as focus groups to delve deeper into the reasoning behind the formation of particular viewpoints, enabling an interpretation of the data that allows for a broader understanding and recognition of important patterns and themes within the discourse (Dandy et al., ; Selge, Fischer, & van der Wal, ). One method that combines both qualitative and semi quantitative analysis of subjective opinion among stakeholders is Q method (Brown, ; Yang, ). Although frequently used in analysis of discourse within the environmental sciences (Brannstrom, ; Hagan & Williams, ; Lansing, ; Walder & Kantelhardt, ) the method has seen very little application in regard to discourse on NNS (Falk‐Petersen, ).…”
Section: Introductionmentioning
confidence: 99%
“…The researcher first informed participants about their rights. Participants were then asked to perform a Q-sorting process on a set of 36 statements regarding engineering learning (Yang, 2016). The Q-sorting statements were adapted from Wheeler's Epistemological Beliefs Survey for Mathematics (EBSM;Wheeler, 2007).…”
Section: Introductionmentioning
confidence: 99%